A study on exemption mechanism status of user charge of in-patient in Ipoh Hospital, Perak, Darul Ridzuan , 1998 - Sabaridah Ismail; Khalib Abd. Latip (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
User charge in health sector will effect individual in the community especially the poor. The implementation of the exemption mechanism is to protect the poor and to ensure the health status of the community. User charge in the health sector was introduced in 1982 but very few study has been done on it. This cross-sectional study was done on in-patient in Ipoh Hospital and provided several useful result. Of 300 respondents) 31.67% of patient were exempted and 69.33% were not exempted. Only 3% of eligible respondent were not exempted. Race) type of job and place of living showed statistically significant with exemp1ion from user charge (p < 0.05). Mu11ivariate statistical tests given race, marital and educational status of the respondent as contributing factor to exemption from user charge. The mean score of the level of knowledge of the respondent regarding exemp1ion from user charge was 11.6 ± 2.3 with 68.3% of the respondent being categorized as having high level of knowledge and 31.70/0 as having low level of knowledge. T test showed no significant correlation between exemp1ion from user charge with the level of knowledge. The mean score for perception towards exemp1ion from user charge was 4.4 ± 1.1 with 78.7% having positive percep1ion and 31.2% having negative perception towards user charge. This different is no significant correla1ion statistically between perception and exemp1ion from user charge. In conclusion, no signjficant correlation was found between exemption from user charge with demographic) socioeconomic, hospital bill. the length of stay. type of ward) the level of knowledge and perception toward the exemp1ion mechanism.